2015
DOI: 10.1002/cne.23907
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructure of geniculocortical synaptic connections in the tree shrew striate cortex

Abstract: To determine whether thalamocortical synaptic circuits differ across cortical areas, we examined the ultrastructure of geniculocortical terminals in the tree shrew striate cortex in order to directly compare the characteristics of these terminals to that of pulvinocortical terminals (examined previously in the temporal cortex of the same species, Chomsung et al. Cerebral Cortex 2010). Tree shrews are considered to represent a prototype of early prosimian primates, but are unique in that sublaminae of striate c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 70 publications
(125 reference statements)
0
13
0
Order By: Relevance
“…The PV‐IR Type I synapses identified in the current study are also unlikely to arise from the amygdala, as the DLPFC receives sparse input from the amygdala (Barbas & De Olmos, ; Miyashita, Ichinohe, & Rockland, ), and PV immunoreactivity within the amygdala appears to be largely restricted to local circuit neurons (Mascagni, Muly, Rainnie, & McDonald, ; Sorvari, Soininen, Paljärvi, Karkola, & Pitkänen, ). However, substantial evidence across multiple species indicates that cortical PV Type I synapses originate from the thalamus (Blümcke, Hof, Morrison, & Celio, ; DeFelipe & Jones, ; del Río & DeFelipe, ; Familtsev et al, ; Freund, Martin, Soltescz, Somogyi, & Whitteridge, ; Freund, Martin, & Whitteridge, ; Jones, ; Jones & Hendry, ; Molinari et al, ; Negyessy & Goldman‐Rakic, ). Thus, although the present study cannot definitively determine that these are exclusively thalamocortical synapses, substantial evidence supports this interpretation.…”
Section: Discussionmentioning
confidence: 99%
“…The PV‐IR Type I synapses identified in the current study are also unlikely to arise from the amygdala, as the DLPFC receives sparse input from the amygdala (Barbas & De Olmos, ; Miyashita, Ichinohe, & Rockland, ), and PV immunoreactivity within the amygdala appears to be largely restricted to local circuit neurons (Mascagni, Muly, Rainnie, & McDonald, ; Sorvari, Soininen, Paljärvi, Karkola, & Pitkänen, ). However, substantial evidence across multiple species indicates that cortical PV Type I synapses originate from the thalamus (Blümcke, Hof, Morrison, & Celio, ; DeFelipe & Jones, ; del Río & DeFelipe, ; Familtsev et al, ; Freund, Martin, Soltescz, Somogyi, & Whitteridge, ; Freund, Martin, & Whitteridge, ; Jones, ; Jones & Hendry, ; Molinari et al, ; Negyessy & Goldman‐Rakic, ). Thus, although the present study cannot definitively determine that these are exclusively thalamocortical synapses, substantial evidence supports this interpretation.…”
Section: Discussionmentioning
confidence: 99%
“…We show that many Po and VPM boutons have an elongated, thick protrusion of the postsynaptic spine head invaginated into them. Two previous 2D electron microscopic studies of lateral geniculate nucleus axon synapses in the primary visual cortex of ferrets 43 and tree shrews 44 reported similar spine profiles, suggesting that spine intrusions may be common in mammalian thalamocortical synapses. While their precise functional significance remains to be determined; our data already provide some intriguing clues.…”
Section: Discussionmentioning
confidence: 70%
“…As described in Section 4, the projections to striate cortex from dLGN layers that receive tectal input (Layers 3 and 6) are distinct from those dLGN layers that do not receive tectal input. Anterograde and retrograde tracer studies have shown that dLGN layers 3 and 6 terminate in the supragranular layers of striate cortex, whereas projections from the remaining dLGN layers (1, 2, 4, and 5) terminate primarily within Layer IV of the striate cortex (Carey, Fitzpatrick, & Diamond, ,; Raczkowski & Fitzpatrick, ; Usrey et al, ; Familtsev et al, ). Also, as described in Section 4, these two layers can be distinguished from the other dLGN layers by their RGC inputs (DeBruyn, ), by the receptive field characteristics of their neurons (Holdefer and Norton, 1995), by cytochrome oxidase histochemistry (Wong‐Riley & Norton, ) and by calcium binding protein labeling (Diamond et al, ).…”
Section: Cortical Projections Of the Tectorecipient Dlgnmentioning
confidence: 99%